DIPLOMASI KEBUDAYAAN INDONESIA MELALUI SEA GAMES 2011 (JAKARTA - PALEMBANG) - Pikri Arif (2012)

(untitled)
Considered effective cultural diplomacy to achieve the national interests of a nation because its implementation is done peacefully without any element of coercion. Sporting events often make the tools to meet the national interests of the nation's sports event regarded as the fastest to show the progress of the nation and the nation's good image in the eyes of the world. Seagames were held in Indonesia made by the Indonesian government as a platform to restore the image of Indonesia in the eyes